The Study of Tooth Preparation Technique Influence on the Quality of Formed Shoulder, Accuracy of Prosthesis Manufacture, and Condition of Supporting Teeth Parodontium after Prosthetics - Shemonaev, Viktor I. (Asian Journal of Pharmaceutics (AJP), 2018)
Purpose: The purpose is to study the quality of a shoulder, the condition of the supporting teeth paradontium and the accuracy of non-removable metal-ceramic structure manufacture after prosthetics, depending on the preparation technique. Materials and Methods: A total of 78 porcelain fused metal crowns were made for 64 patients. The total number of patients was randomly divided into two equivalent groups of 32 people. In the first group (Group A), tooth preparation was performed according to the traditional method. The preparation of teeth in the second group (Group B) was performed using the developed algorithm. The marginal abutment of the crowns was measured after the obtaining of digital photographs with a calibrated microscope. The quality of the shoulder was estimated using the author’s technique, which presupposes three-dimensional scanning and color staining of the tooth stump model. Periodontal status was assessed by the amount of gingival fluid measured by the area of filter paper strip impregnation immersed in the gingival sulcus after obtaining the digital photographs. Results: The average values obtained for each group were the following ones: The shoulder quality - Group A = 67.27% (standard deviation [SD]: 4.64%) and Group B = 74.96 (SD: 5.83%), fitting accuracy - Group A = 78, 18 μm (SD: 6.83 μm) and Group B = 69.58 μm (SD: 6.83 μm), and the amount of gingival fluid - Group A = 0.621 mm2 (SD: 0.04 mm2) and Group B = 0.598 mm2 (SD: 0.05 mm2). Pearson’s statistical analysis showed a significant difference in shoulder quality and the accuracy of crown fitting in Groups A and B (P < 0.05). An insignificant relationship was shown for the criterion of gingival fluid volume in the Groups A and B (P > 0.05). Conclusion: The use of the developed algorithm of the tooth preparation for permanent orthopedic constructions allows to obtain a statistically significant increase of the shoulder quality and the accuracy of crown fitting in comparison with the traditional preparation method.